Foreign direct investment in Africa: The role of natural resources, market size, government policy, institutions and political instability - Elizabeth Asiedu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Data from several investor surveys suggest that macroeconomic instability, investment restrictions, corruption and political instability have a negative impact on foreign direct investment (FDI) to Africa. However, the relationship between FDI and these country characteristics has not been studied. This paper uses panel data for 22 countries over the period 1984-2000 to examine the impact of natural resources, market size, government policies, political instability and the quality of the host country's institutions on FDI. It also analyses the importance of natural resources and market size vis-à-vis government policy and the host country's institutions in directing FDI flows. The main result is that natural resources and large markets promote FDI. However, lower inflation, good infrastructure, an educated population, openness to FDI, less corruption, political stability and a reliable legal system have a similar effect. A benchmark specification shows that a decline in the corruption from the level of Nigeria to that of South Africa has the same positive effect on FDI as increasing the share of fuels and minerals in total exports by about 35 per cent. These results suggest that countries that are small or lack natural resources can attract FDI by improving their institutions and policy environment. – Africa ; corruption ; foreign direct investment ; institutions ; natural resources ; political instability
Keywords: F23; O55; 330; Direktinvestition; Korruption; Natürliche Ressourcen; Wirtschaftslage; Afrika; Politische Stabilität